Recording Spikes Activity in Cultured Hippocampal Neurons Using Flexible or Transparent Graphene Transistors - Veliev, Farida; Han, Zheng; Kalita, Dipankar; Briançon-Marjollet, Anne; Bouchiat, Vincent; Delacour, Cécile (Frontiers in Neuroscience, 2017)
The emergence of nanoelectronics applied to neural interfaces has started few decades ago, and aims to provide new tools for replacing or restoring disabled functions of the nervous systems as well as further understanding the evolution of such complex organization. As the same time, graphene and other 2D materials have offered new possibilities for integrating micro and nano-devices on flexible, transparent, and biocompatible substrates, promising for bio and neuro-electronics. In addition to many bio-suitable features of graphene interface, such as chemical inertness and anti-corrosive properties, its optical transparency enables multimodal approach of neuronal based systems, the electrical layer being compatible with additional microfluidics and optical manipulation ports. The convergence of these fields will provide a next generation of neural interfaces for the reliable detection of single spike and record with high fidelity activity patterns of neural networks. Here, we report on the fabrication of graphene field effect transistors (G-FETs) on various substrates (silicon, sapphire, glass coverslips and polyimide), exhibiting high sensitivity (4mS/V) and low noise level (10-22 A²/Hz). We demonstrate the in-vitro detection of the spontaneous activity of hippocampal neurons in-situ-grown on top of the graphene sensors during several weeks in a microfluidic chamber. These results provide an advance towards the realization of biocompatible devices for reliable and high spatio-temporal sensing of neuronal activity for both in-vitro and in-vivo applications.